Development of Snakes and Ladders Learning Media Based on Joyful Learning in Islamic Religious Education Subjects - Salsabila, Sari; Soraya, Irma; Hamdani, Asep Saepul (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
Islamic Religious Education (PAI) at the senior high school level continues to face challenges in enhancing student motivation and engagement, primarily due to monotonous and minimally interactive instructional methods. To address this issue, the present study aims to develop a learning medium in the form of a Snakes and Ladders game based on a joyful learning approach, integrated with question and challenge cards, and to assess its feasibility through expert validation and limited trials. Employing a Research and Development (R&D) framework, this study adopts the ADDIE model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The learning medium is designed based on the thematic content of Q.S. al-Māidah / 5:48, which emphasizes competing in goodness, and Q.S. at-Taubah / 9:10, which highlights the Islamic work ethic. Validation by media experts yielded an average score of 3.85, while material experts assigned a score of 3.71, both categorized as “highly feasible.” Implementation in Grade X of senior high school demonstrated that the media enhanced students’ conceptual understanding, encouraged healthy social interactions, and nurtured their learning spirit. Despite certain limitations, such as time constraints and the dominance of the game-related elements, the media effectively supported an active and enjoyable learning process. Therefore, the snakes and ladders-based learning medium presents a promising pedagogical innovation for contextualizing Islamic Religious Education and reinforcing character development among high school students. Keywords: Learning Media, Snakes and Ladders, Joyful Learning, Islamic Religious Education